2020
DOI: 10.3892/etm.2020.9018
|View full text |Cite
|
Sign up to set email alerts
|

Post‑infectious irritable bowel syndrome after a laboratory‑proven enteritis

Abstract: There are scarce data on risk factors for post-infectious irritable bowel syndrome (PI-IBS). The objective of this study was to determine the risk factors of developing PI-IBS following an acute infectious gastroenteritis (AGE) episode in which, by laboratory tests, the etiological agent was isolated. The study was conducted on patients admitted to a tertiary center of infectious diseases during three consecutive years. The patients were divided into two groups: a group consisting of patients admitted with AGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…As shown in Table 1 , based on data from 29 studies, 3.7% to 85.5% of subjects with AGE due to different causes developed PI-IBS; 10 - 39 this incidence rates were much higher than the development of IBS among the control population in 16 studies (0.3% to 23.3%). 10 In a recent meta-analysis, the pooled prevalence of PI-IBS was 11.5% (2,217/21,421; 95% confidence interval, 8.2 to 15.8); the prevalence was comparable in the studies reporting prevalence at 3, 6, 12, 13–59, or ≥60 months after AGE.…”
Section: Epidemiology Of Pi-ibsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Table 1 , based on data from 29 studies, 3.7% to 85.5% of subjects with AGE due to different causes developed PI-IBS; 10 - 39 this incidence rates were much higher than the development of IBS among the control population in 16 studies (0.3% to 23.3%). 10 In a recent meta-analysis, the pooled prevalence of PI-IBS was 11.5% (2,217/21,421; 95% confidence interval, 8.2 to 15.8); the prevalence was comparable in the studies reporting prevalence at 3, 6, 12, 13–59, or ≥60 months after AGE.…”
Section: Epidemiology Of Pi-ibsmentioning
confidence: 96%
“…As shown in Table 1 , infection with bacterial, viral, and protozoal agents causing AGE has been reported to be followed by PI-IBS. 11 - 39 Among bacteria, infection with organisms causing dysentery such as Shigella is more likely to result in PI-IBS than others. 10 However, recently, even bacterial pathogens that conventionally do not invade the gut mucosa, such as Vibrio cholerae are also shown to cause PI-IBS.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…The prevalence of PI-IBS is approximately 4%-36% in patients with previous infectious gastroenteritis and is higher in females, young people, patients who experienced severe infections and individuals with psychological comorbidities. Moreover, some pathogens seem more predisposing than others; indeed, bacterial infections (particularly by Campylobacter , Shigella , Escherichia coli and Salmonella ) are more likely to enhance PI-IBS than viruses and other microorganisms[ 34 , 44 , 45 ]. The pathogenesis of this condition is poorly understood, but it is hypothesized that the responsible pathogenic microorganism may trigger an immunologic and inflammatory response with low-grade inflammation and mucosal injury, which causes the prolongation of IBS symptoms in predisposed individuals.…”
Section: Ibsmentioning
confidence: 99%
“…14,17 In the study by Lacob and colleagues, comparing patients with PI-IBS with a control group showed that women had a 4.4-fold increased odds of developing PI-IBS (versus men). 20 This can be because of the increased level of psychological disorders in women, including depression, anxiety, and stress, which have been identified as important factors predisposing the patient to PI-IBS. 21 Younger age has also been introduced as a predisposing factor for PI-IBS, and age > 50-60 years old has been suggested to protect against PI-IBS, possibly because of the poorer activation of the immune system.…”
Section: Discussionmentioning
confidence: 99%